Using IEEE standards to support America's Army gaming development - Land, S.K.; Wilson, B. (Computer (Long Beach, Calif.), 2006)
IEEE software and systems engineering (SS&E) standards support basic software production control processes. When practically applied, these standards helped resolve the real-world problems that occurred when researchers combined a classically structured Department of Defense (DoD) approach to basic skills trainer (BST) development with the more agile environment of gaming systems development. These IEEE standards directly aided the development of sound software engineering practices and processes. They provided the flexible support necessary for this dynamic and fast-paced integration environment while promoting the practical process application that helped to develop the America's Army products. A computer game produced by the US Army, AA promotes army recruiting and the seven core values of loyalty, duty, respect, selfless service, honor, integrity, and personal courage. The game's PC version currently boasts more than 7.5 million registered players worldwide